Guided Discovery Learning for Acid-Base Chemistry: Effects on Student Achievement and Conceptual Mastery - Heti Nurhayati; Majid Shabani Mahalli (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the effect of guided discovery learning on students’ chemistry learning outcomes and conceptual understanding in acid-base topics, addressing challenges in mastering abstract chemical concepts through structured experimental activities. Methodology: A quasi-experimental design with a non-equivalent control group was employed. The experimental group received guided discovery learning integrated with laboratory activities, while the control group followed conventional instruction. Data were collected through pre-tests, post-tests, and observation sheets, and analyzed using descriptive statistics, independent sample t-tests, N-gain, and effect size (Cohen’s d) with SPSS software. Main Findings: Results show that the experimental group achieved higher post-test scores (Mean = 82.15, N-gain = 0.67) compared to the control group (Mean = 70.21, N-gain = 0.45), with a statistically significant difference (p = 0.001) and a large effect size (Cohen’s d = 0.82). Guided discovery learning effectively improves students’ conceptual understanding and overall chemistry learning outcomes. Novelty/Originality of this study: This study integrates guided discovery learning with systematically designed laboratory activities in acid-base instruction, providing a holistic evaluation of learning improvement. The approach connects theoretical concepts with practical experiences, offering a more effective instructional model and contributing new knowledge for enhancing chemistry education practices in secondary schools.